Nanofunctionalised orthopaedic implants - Mirza, Farhan A. (Cranfield University, 2018)
Due to an aging population and younger patients presenting with musculoskeletal disorders, there is a need for orthopaedic implants with improved healing rates and longer implant life. Numerous research has developed implant surfaces with micro-topography and biomolecules to imitate the native extra cellular matrix (also known as biomimetic surfaces). This research has utilised such a biomimetic approach by immobilising the cell adhesive peptide, RGD (Arginine-Glycine-Aspartic Acid), to a titanium alloy Ti6Al4V surface. This research polymerised Hyperbranched Polyglycerol (HBPG) from the titanium surface using Ring Opening Multi-Branching Polymerisation (ROMBP). HBPG is a biologically compatible and non-toxic synthetic biopolymer, able to reduce non-specific protein adsorption, increase the titanium surface wetting (hydrophilicity), thereby limiting foreign body reactions. Extensive hydroxyl groups at the periphery of HBPG provides conjugation sites for biomolecule attachment. In this work the RGD peptide was conjugated to the polymer via a siloxane layer. This research developed a novel passivation solution for the preparation of the titanium alloy surface, using a mixture of hydrogen peroxide and nitric acid (a passivation mixture not used in the literature). This novel mixture was shown to etch the titanium surface, producing micro and nano surface features, both of which have been shown to improve cellular function in the literature. The hydrogen peroxide/nitric acid solution showed extensive oxidising ability on titanium, leading to the formation of reactable hydroxyl groups. Contact-angle measurements showed that the novel passivating solution produces a hydrophilic surface similar to that of peroxidation for 12-hours, but achieved in only 2-hours. In conjunction with the etching and oxidising abilities of hydrogen peroxide, the nitric acid reacts with the titanium surface, leading to the formation of a protective titanium oxide layer, enhancing corrosion resistance and improving biocompatibility. Biological investigations with the pre-osteoblast cell line MC3T3-E1 showed greater osteoblast cell attachment and adhesion strength, as well as improved bone matrix mineralisation on the passivated titanium surface functionalised with HBPG and the RGD peptide, compared to the raw and passivated titanium surfaces. Antibacterial testing of HBPG revealed substantially reduced bacterial cell colonies on the passivated/polymerised titanium surface, possibly arising from electrostatic and hydrophobic repulsion. This research has successfully developed a new titanium passivation solution (hydrogen peroxide/nitric acid) that can yield a contact-angle of around 35° in just 2-hours, rivalling the Piranha solution. The successful immobilisation of a cyclic RGD (cyclic-RGDfc) to a titanium surface functionalised with HBPG, has been shown in this research to drastically improve mineralised bone matrix production from the MC3T3-E1 cell line. This indicates earlier osseointegration of the implant may be possible, thereby improving patient healing times.
Keywords: Adhesion; antibacterial; attachment; biomimetic; biomolecule; detachment; glycidol; hydrophilic; hydroxyapatite; hyperbranched; implant; integrin; mineralisation; nano; orthopaedic; osseointegration; osteoblasts; osteoconduction; osteoid; osteoinduction; passivation; polyglycerol; polymerisation; proliferation; RGD; roughness; titanium